Tuberculosis Misdiagnosed as Bronchogenic Carcinoma: A Case Report - Pejman Hosseinzadeh; Sara Samadi; Shirin Taraz Jamshidi; Sayed Mortaza Fayez; Mahnaz Mozdourian (Clinical Case Reports, 2026)
ABSTRACT The patient, a 77‐year‐old male smoker, presented to the Emergency Department with dyspnea, cough, fever, night sweats, and 12 kg weight loss, initially suggesting COPD or lung cancer. Chest CT revealed a right upper lobe mass, pleural effusion, and lymphadenopathy, prompting suspicion of malignancy. Bronchoalveolar lavage was negative for acid‐fast bacilli (AFB), and abdominal/pelvic CT showed no metastases. Transthoracic biopsy confirmed pulmonary TB with caseating granulomas and AFB, with no evidence of malignancy. A 6‐month anti‐TB regimen resolved all symptoms and lesions.